Environmental Value Engineering (EVE) Assessment: A Case Study of Comparing Curtain Wall System Alternatives - Adamtey, Simon Asinor (International Journal of Sustainable Construction Engineering and Technology, 2021)
The need to explore environmentally friendly materials to avoid the depletion of the non-renewable resources is very significant. Humans have been heavily dependent on non-renewable resources since the industrial revolution.  This has led to environmental impacts such as increase in CO2 in the atmosphere and global warming, which is arguably one of the major problems we are facing today.  Faced with the possible shortages of natural resources, pollution, population overgrowth, and concern for protecting the environment, human beings are coming to realize that new concepts are needed to analyze the interdependent parts of the built environment. Considering the present need for optimal use of our resources, as opposed to maximizing, there is an increasing shift of focus to system evaluation methodologies that can be used to evaluate the environmental impact of a product or system. It is with this ever-increasing need for products that are not only functional and cost-effective, but also environmental friendly, that Environmental Value Engineering (EVE) assessment is gaining popularity.This paper explores the application of the EVE methodology through a case study of comparing the environmental impact of the C.T.W. Series 3 Wood Hybrid Curtain Wall system and the Kawneer 1600 Wall System. The EVE methodology, which is an environmental life cycle assessment method, was used to compare the inputs of the environment, fuel energy, goods, and services in terms of emergy for both systems.